Facile Post‐Synthetic Modification of Amine‐Functionalized Metal‐Organic Frameworks to Integrate Visible‐Light Responsive Pt Complexes for Hydrogen Evolution Reaction. Issue 12 (5th September 2019) - Lionet, Zakary; Kim, Tae‐Ho; Horiuchi, Yu; Lee, Soo Wohn; Matsuoka, Masaya
Abstract: Integration of photocatalytic polypyridyl complexes inside metal‐organic frameworks (MOFs) backbone has been so far mostly achieved by utilization of bipyridine dicarboxylic acid as a linker. This fact limits the possibility of hosts that can be used amongst the countless MOFs existing. In this study, by using UiO‐66‐NH2 as a stable platform, postsynthetic modification (PSM) of the amino groups in organic linkers with 2‐pyridinecarboxaldehyde and K2 PtCl4 was applied to create a N, N ‐chelating ligand and simultaneous coordination of Pt 2+ ions in a one‐pot approach. XAFS and 1 H NMR analyses confirmed the creation of pyridylimine Pt(II) complexes. The composites showed viable activity towards photocatalytic hydrogen evolution reaction under visible light irradiation. Recyclability and leaching tests demonstrated their high stability and function as heterogeneous catalysts. Abstract : Linked‐up : Introduction of pyridyl Pt(II) complexes using a facile postsynthetic modification was performed into basic metal‐organic frameworks with amino groups. The composites showed visible light absorption properties due to the newly integrated complex and photoactivity for hydrogen evolution reaction under visible light irradiation.